1994
DOI: 10.1029/93rs01828
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic behavior of ionospheric scintillation: Modeling and observations

Abstract: Abstract. The chaotic, but nondeterministic, structure of the ionosphere and radio wave amplitude and phase scintillation measured on the ground have been simulated using the phase screen model with the power law spectrum of random Gaussian phase fluctuations. Comparison of the information dimension calculated for phase fluctuations on a screen with that for amplitude scintillation at the receiver shows that the original chaotic structure in the ionosphere is completely masked by the propagation effects. Hence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…The presence of chaos is indicated by the positive values of the Lyapunov exponent found in all the computations for all the TEC values obtained for the selected days for all the measuring stations used in this work. This can be expected, as it agrees with results from previous works that show that there is a reasonable presence of chaos in the ionosphere, even in the midst of the influence of stochastic drivers like solar winds (Bhattacharyya, 1990;Wernik and Yeh, 1994;Kumar et al, 2004;Unnikrishnan et al, 2006a, b;Unnikrishnan, 2010).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The presence of chaos is indicated by the positive values of the Lyapunov exponent found in all the computations for all the TEC values obtained for the selected days for all the measuring stations used in this work. This can be expected, as it agrees with results from previous works that show that there is a reasonable presence of chaos in the ionosphere, even in the midst of the influence of stochastic drivers like solar winds (Bhattacharyya, 1990;Wernik and Yeh, 1994;Kumar et al, 2004;Unnikrishnan et al, 2006a, b;Unnikrishnan, 2010).…”
Section: Discussionsupporting
confidence: 81%
“…Also, Wernik and Yeh (1994) further revealed the chaotic behavior of the ionospheric turbulence using scintillation data and numerical modeling of scintillation at high latitudes. They showed that the ionospheric turbulence attractor (if it exists) cannot be reconstructed from amplitude scintillation data, and their measured phase scintillation data adequately reproduce the assumed chaotic structure in the ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Bhattacharyya (1990) had studied the chaotic behavior of ionospheric density fluctuations, using amplitude and phase scintillation data, and found the existence of lowdimensional chaos. Also, Wernik and Yeh (1994) have studied chaotic behavior of ionospheric turbulence using scintillation data and numerical modeling of scintillation at high latitude. Kumar et al (2004) reported the evidence of low dimensional chaos in a set of TEC data, obtained by Faraday rotation technique, measured at a high-latitude station, Goose Bay (47 • N, 286 • E), during the period, February to April 1976.…”
Section: Introductionmentioning
confidence: 99%
“…The largest Lyapunov exponent (λ 1 ) can be used to determine the rate of divergence as indicated by Wolf et al (1985), where…”
Section: Lyapunov Exponentsmentioning
confidence: 99%
“…These previous efforts made by the aforementioned researchers has led to the development of the concept of investigating and revealing the chaoticity and the complex dynamics of the ionosphere, and as a result, studies on the chaoticity of the ionosphere have been conducted, by some investigators like Bhattacharyya (1990), who studied chaotic behaviour of ionospheric diversity fluctuation using amplitude and phase scintillation data, and found the existence of low-dimension chaos. Also, Wernik and Yeh (1994) further revealed the chaotic behaviour of the ionospheric turbulence using scintillation data and numerical modelling of scintillation at high latitude. They showed that the ionospheric turbulence attractor (if it exists) cannot be reconstructed from amplitude scintillation data, and their measured phase scintillation data adequately reproduce the assumed chaotic structure in the ionosphere.…”
mentioning
confidence: 99%